Complications of HIPEC for ovarian cancer surgery: evaluation over two time periods - Navarro Santana, Beatriz; Garcia-Torralba, Esmeralda; Viveros-Carreño, David; Rodriguez, Juliana; Pareja, Rene; Martin, Alicia; Forte, Sara; Krause, Kate J; González-Martín, J M; Ramirez, Pedro T (International journal of gynecological cancer, 2024)
ObjectiveCytoreductive surgery in conjunction with hyperthermic intraperitoneal chemotherapy (HIPEC) is being explored in the upfront, interval, and recurrent setting in patients with ovarian cancer. The objective of this systematic review was to assess the rate of complications associated with HIPEC in epithelial ovarian cancer surgery over two time periods.MethodsThis study was registered in PROSPERO (CRD42022328928). A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist. Ovid/Medline, Ovid/Embase, Web of Science, Scopus, and Cochrane Central Register of Controlled Trials were searched from January 2004 to April 2022. We included studies reporting on patients with advanced primary or recurrent epithelial ovarian cancer who underwent cytoreductive surgery and HIPEC. We evaluated two different time periods: 2004–2013 and 2014–2022. A random-effects meta-analysis was used to produce an overall summary. Subgroup analyses were planned according to recruited period for each specific complication type. Heterogeneity was assessed using the I2 statistic.ResultsA total of 4928 patients were included from 69 studies for this systematic review; 19 published from 2004–2013, and 50 published from 2014–2022. No significant differences were found between the two time periods in terms of blood transfusions (33% vs 51%; p=0.46; I2=95%) overall gastrointestinal complications (15% vs 21%; p=0.36; I2=98%), infectious diseases (16% vs 13%; p=0.62; I2=93%), overall respiratory complications (12% vs 12%; p=0.88; I2=91%), overall urinary complications (6% vs 12%; p=0.06; I2=94%), or thromboembolic events (5% vs 3%; p=0.25; I2=63%). Also, no differences were found in intensive care unit (ICU) admissions (89% vs 28%; p=0.06; I2=99%), reoperations (8% vs 7%; p=0.50; I2=37%), or deaths (3% vs 3%; p=0.77; I2=57%).ConclusionsOur review showed that overall complications have not changed over time for patients undergoing HIPEC in the setting of primary or recurrent ovarian cancer. There was no decrease in the rates of ICU admissions, reoperations, or deaths.